Comparative analysis of earned value management techniques in construction projects - Mohamed Elsaid; Khaled Nassar; Fahad K. Alqahtani; Ibrahim Abotaleb (Scientific Reports)
Abstract Several earned value techniques are used to monitor progress and forecast the cost and time performance of construction projects. However, their forecasting accuracy, particularly across different project types and progress stages, remains understudied. This study evaluates the predictive accuracy of three earned value techniques: Earned Duration, Earned Schedule, and Planned Value—across a diverse dataset of 30 construction projects. The overarching objective is to evaluate the accuracy of these techniques in predicting project completion dates and to discern the most effective method based on project duration percentages. The findings reveal that Earned Schedule provides the most accurate predictions during early project stages, while Earned Duration is more reliable at later stages. The results emphasize the importance of considering project type and progress level when selecting a forecasting method. Practical guidelines are proposed to assist project managers in choosing the most effective technique at different stages of project development. By refining forecasting accuracy and providing strategic guidelines, this research serves as a valuable resource for achieving enhanced project outcomes across diverse construction projects.